Answer:
-11x+12
Step-by-step explanation:
(x^2-4x+3)-(x^2+7x-9)
x^2-x^2-4x-7x+3-(-9)
-11x+3+9
-11x+12
Answer:
x= 10 and y= -1
Step-by-step explanation:
Rewrite your second equation Y= -2x+ 19 then plug it into the first equation.
x- (-2x + 19) = 11
x + 2x - 19 =11
3x - 19 = 11
3x = 30
x = 10
The plug that answer into the first equation and solve.
10 - y = 11
-y = 1
y = -1
The answer is A the perimeter of rectangle A is z times the perimeter of rectangle B
6/x = x-1
Multiply x by both sides
6= x(x-1)
Set x and x-1 equal to 6
x = 6, x = 1+6 = 7
1st year= 18000 x 0.85 = 15300
2nd year= 15300 x 0.85 = 13005
3rd year= 13005 x 0.85= 11054.25